THE EFFECT OF SERVICE QUALITY, PRICE, AND PROMOTION ON APPLICATION-BASED ONLINE TRANSPORTATION CUSTOMER LOYALTY CASE STUDY ON GOJEK CUSTOMERS IN SEMARANG CITY - Samsudin, Rohmat; Suhaji, Suhaji (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyse the effect of service quality, price, and promotion on application-based online transportation customer loyalty, especially for Gojek users in Semarang City. The three independent variables were chosen because they are believed to have a strategic role in maintaining and increasing customer loyalty amid the increasingly competitive digital transportation industry. This research uses a quantitative approach with a survey method through a questionnaire to 100 respondents who are active users of Gojek services. The analysis technique used is multiple linear regression with the help of SPSS to test the partial and simultaneous effects of the independent variables on customer loyalty as the dependent variable. The results showed that service quality, price, and promotion have a positive and significant effect on customer loyalty, both partially and simultaneously. Service quality is the most dominant variable in shaping user loyalty. These findings are expected to be a reference for online transport companies in developing marketing strategies that are oriented towards customer experience.